Brachycaudus lucifugus n. sp., eine Wurzellaus am Spitzwegerich (Plantago lanceolata L.) (Homoptera: Aphididae). - Müller, Fritz Paul (Contributions to Entomology = Beiträge zur Entomologie, 1955)
Nomenclatural Actslucifugus Müller, 1955 (Brachycaudus), spec. n.